Creation of a global emergency-department research network: a feasibility study. (March 2019) - Mahajan, Prashant; Bhoi, Sanjeev; Kumar, Vijaya Arun; Ma, Qingbian; Menon, Vidya; Ng, Chip Jin; Oteng, Rockfeller; Perondi, Beatriz; Belle, Apoorva; Neumar, Robert
Abstract: Background: The epidemiology of emergency care globally is largely unknown, especially in developing countries, because of a lack of common taxonomy, an absence of robust reporting mechanisms, and because emergency medicine is not always recognised as a subspecialty in its own right. Other disease-specific and specialty-specific research networks have addressed these barriers and brought about improved health of populations as a result. The University of Michigan's Department of Emergency Medicine is developing an international emergency-department research network to study the epidemiology of emergency visits in developed and developing countries. Our objectives are: to describe the first steps taken in creation of an international emergency-department research network; to discuss lessons learned; and propose a feasibility pilot study to determine epidemiology of emergency department visits across ten emergency departments in eight countries. Methods: We contacted emergency departments that have a training programme for emergency medicine and have an existing collaboration with the University of Michigan's Global Reach programme in China, India, Ghana, Brazil, Taiwan, Austria, Finland, and the USA. We conducted a survey of research-related resources and electronic data access to determine whether sites were suitable for inclusion in the network. Finally, we proposed a feasibility study to measure interest in the project at sites as well as their ability to participate. Findings: We noticed substantial variation between sites with respect to: the emergency department triage process; access to consultants; definitions of levels of severity of illness; management of resuscitation; and discharge disposition, even for the same condition. We developed a manual of operations, standard taxonomies, and are working on Institutional Review Board approval and data transfer agreements. We will be enrolling patients in prospective and retrospective studies with a sparse simultaneous-sampling design over a period of 6 months. The data collected will have ongoing quality checks to confirm validity and reliability. Interpretation: Despite some substantial barriers, development of an infrastructure to study emergency care at a global level is feasible. The sustainability plan is to create a robust network that nurtures future investigators, identifies funding sources, and works on collaborative research. We anticipate challenges in collecting baseline data on emergency department presentations, so have designed two pathways to collect data: a retrospective Electronic Health Record query; and prospective data collection in real-time. We are planning an in-person meeting to establish standard processes for research priorities and resource allocation. Funding: None.